2021
DOI: 10.3390/ijerph18094991
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Comparison of Physical Activity during COVID-19 in a Sample of Rural and Non-Rural Participants in the US

Abstract: Physical activity (PA) pre-COVID-19 was lower in rural areas compared to non-rural areas. The purpose of this study was to determine COVID-19’s impact on PA in rural and non-rural residents. A cross-sectional study consisting of a convenience sample of 278 participants (50% rural, 50% non-rural) from 25 states completed an online survey describing their PA behaviors and perceptions during COVID-19. The global physical activity questionnaire was used to determine PA in various domains and summed to determine if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 31 publications
6
9
1
Order By: Relevance
“…Our finding that education and living environment are important determinants and correlates of PA replicates results from earlier studies [35,36] and ecological models [37]. For example, it has been shown that education was a correlate of moderate-tovigorous PA during COVID-19 in Canada [29] and living in urban areas increased the risk for inactivity during COVID-19 in US adults and Croatian adolescents [38,39]. In general, individuals from urban areas are more physically active [40,41], frequently engaged in sports clubs and, due to the living area and shortage of green space, are more dependent on sport facilities.…”
Section: Discussionsupporting
confidence: 88%
“…Our finding that education and living environment are important determinants and correlates of PA replicates results from earlier studies [35,36] and ecological models [37]. For example, it has been shown that education was a correlate of moderate-tovigorous PA during COVID-19 in Canada [29] and living in urban areas increased the risk for inactivity during COVID-19 in US adults and Croatian adolescents [38,39]. In general, individuals from urban areas are more physically active [40,41], frequently engaged in sports clubs and, due to the living area and shortage of green space, are more dependent on sport facilities.…”
Section: Discussionsupporting
confidence: 88%
“…In rural areas, it is often easier to find suitable areas for sports activity, even within a limited radius, and usually rural houses and apartments also offer more space to practice PA. This conjecture is confirmed by Beck et al [ 137 ]. A comparison between people from urban and rural areas revealed a positive impact of living in rural areas [ 138 ].…”
Section: Discussionsupporting
confidence: 76%
“…In order to minimize the number of variables, educational level was used as a surrogate to income as they were highly correlated. To define rurality, each participant’s zip code was compared to the Rural-Urban Continuum Codes (RUCC) [ 30 ]—a code of four or higher was operationally defined as rural [ 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%